Related Effects of Methamphetamine on the Intestinal Barrier via Cytokines, and Potential Mechanisms by Which Methamphetamine May Occur on the Brain-Gut Axis - Li, Yuansen; Kong, Deshenyue; Bi, Ke; Luo, Huayou (Frontiers in Medicine, 2022)
Methamphetamine (METH) is an illegal drug widely abused in many countries. Methamphetamine abuse is a major health and social problem all over the world. However, the effects of Methamphetamine on the digestive system have rarely been reported. Previous studies and clinical cases have shown that methamphetamine use can lead to the impaired intestinal barrier function and severe digestive diseases. Methamphetamine can cause multiple organ dysfunction, especially in the central nervous system (CNS). The gut microbiota is involved in the development of various central nervous system-related diseases via the gut-brain axis (GBA). Here, we describe the related effects of methamphetamine on the intestinal barrier via cytokines and the underlying mechanisms by which METH may occur in the brain-gut axis.